1988
DOI: 10.1073/pnas.85.20.7675
|View full text |Cite
|
Sign up to set email alerts
|

Human ETS2 gene on chromosome 21 is not rearranged in Alzheimer disease.

Abstract: The human ETS2 gene, a member of the ETS gene family, with sequence homology with the retroviral ets sequence of the avian erythroblastosis retrovirus E26 is located on chromosome 21. Molecular genetic analysis of Down syndrome (DS) patients with partial trisomy 21 allowed us to reinforce the supposition that ETS2 may be a gene of the minimal DS genetic region. It was originally proposed that a duplication of a portion of the DS region represents the genetic basis of Alzheimer disease, a condition associated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The ETS2 gene is translocated from chromosome 21 to chromosome 8 in the specific translocation t(8;21) known to be associated with acute myelogenous leukemia (8,9). The location of the ETS2 gene at 21q22 has suggested that it may be a contributing genetic element in the cluster of genes whose amplification is associated with Down syndrome (DS) (9,10), and this concept is supported by the observation that the ETS2 gene is found in three copies in partial trisomies 21 associated with the DS phenotype (11,12).…”
supporting
confidence: 49%
“…The ETS2 gene is translocated from chromosome 21 to chromosome 8 in the specific translocation t(8;21) known to be associated with acute myelogenous leukemia (8,9). The location of the ETS2 gene at 21q22 has suggested that it may be a contributing genetic element in the cluster of genes whose amplification is associated with Down syndrome (DS) (9,10), and this concept is supported by the observation that the ETS2 gene is found in three copies in partial trisomies 21 associated with the DS phenotype (11,12).…”
supporting
confidence: 49%
“…etsl is amplified in a myelodisplastic syndrome (Ohyashiki et al, 1990). Extra dosage of ets2 may increase susceptibility to leukemia in Down's syndrome (Sacchi et al, 1988). The Ets2 mRNA level increases in an acute nonlymphoblastic leukemia (Santoro et al, 1992).…”
Section: Transformation By Ets Family Members Vets Induces Erythroblamentioning
confidence: 99%
“…The (59). Although no direct evidence links altered CD11/ CD18 expression to leukemogenesis per se, a large body of data suggests that cell-cell and cell-matrix interactions (some mediated by P2 integrins) are important in regulating differentiation and maturation of hematopoietic cells (52).…”
mentioning
confidence: 99%